Experience of using of instruments MAXI for computer-aided control of the casting structure from annealed and high-test cast iron by magnetic method - S. G. Sandomirski; L. Z. Pisarenko; S. F. Lukashevich (Литьë и металлургия)
The magnetic analyzer of production structure quality (MAXI-P) is created and applied in industry at ОАО "MZOO"The result of measuring is compared with the previously established usability ranges. By the result is comparison the signal of actuating mechanism operating is formed for separation of articles for non-defective and defective. The interconnection of ferrite contents in foundry goods and instrumentation indications of MAXI-P is established.